Detection of hydrogen peroxide with chemiluminescent micelles - Dongwon Lee (Dove Medical Press, 2008)
Dongwon Lee1, Venkata R Erigala1,3, Madhuri Dasari1, Junhua Yu2, Robert M Dickson2, Niren Murthy11The Wallace H. Coulter Department of Biomedical Engineering; 2Department of Chemistry and Biochemistry, Georgia Institute of Technology, Atlanta, GA, USA; 3The Scripps Research Institute, La Jolla, CA, USAAbstract: The overproduction of hydrogen peroxide is implicated in the progress of numerous life-threatening diseases and there is a great need for the development of contrast agents that can detect hydrogen peroxide in vivo. In this communication, we present a new contrast agent for hydrogen peroxide, termed peroxalate micelles, which detect hydrogen peroxide through chemiluminescence, and have the physical/chemical properties needed for in vivo imaging applications. The peroxalate micelles are composed of amphiphilic peroxalate based copolymers and the fluorescent dye rubrene, they have a ‘stealth’ polyethylene glycol (PEG) corona to evade macrophage phagocytosis, and a diameter of 33 nm to enhance extravasation into permeable tissues. The peroxalate micelles can detect nanomolar concentrations of hydrogen peroxide (>50 nM) and thus have the sensitivity needed to detect physiological concentrations of hydrogen peroxide. We anticipate numerous applications of the peroxalate micelles for in vivo imaging of hydrogen peroxide, given their high sensitivity, small size, and biocompatible PEG corona.Keywords: hydrogen peroixde, chemiluminescence, micelles, amphiphilic copolymer